Validation of a frailty index in patients undergoing curative surgery for urologic malignancy and comparison to other risk stratification tools - Lascano, Danny (Urol Oncol, 2015)
OBJECTIVE: To retrospectively validate and compare a modified frailty index predicting adverse outcomes to other risk stratification tools among patients undergoing urologic oncological surgeries. MATERIALS AND METHODS: The American College of Surgeons National Surgical Quality Improvement Program was queried from 2005–2013 to identify patients undergoing cystectomy, prostatectomy, nephrectomy, and nephroureterectomy. Using the Canadian Study of Health & Aging Frailty Index, 11 variables were matched to the database; 4 were also added due to their relevance in oncology patients. The incidence of mortality, Clavien-Dindo IV complications, and adverse events were assessed with patients grouped according to their modified frailty index score. RESULTS: A total of 41,681 cases of patients were identified undergoing surgery for presumed urological malignancy. Patients with a high frailty index score of >0.20 had a 3.70 odds of a Clavien-Dindo IV event (CI: 2.865–4.788, p<0.0005) and a 5.95 odds of 30-day mortality (CI: 3.72–9.51, p<0.0005) in comparison to non-frail patients after adjusting for race, gender, age, smoking history and procedure. Using C-statistics to compare the sensitivity and specificity of the predictive ability of different models per risk stratification tool and Akaiki Information Criteria to assess for the fit of the models with the data, the modified frailty index was comparable or superior to the Charlson Comorbidity Index but inferior to the American Society of Anesthesiologists Risk Class in predicting 30-day mortality or Clavien-Dindo IV events. When the modified frailty index was augmented with the American Society of Anesthesiologists Risk Class, the new index was superior in all regards in comparison to risk stratification tools. CONCLUSION: Existing risk stratification tools may be improved by incorporating variables in our 15 point modified frailty index as well as other factors such as walking speed, exhaustion, and sarcopenia to fully assess frailty. This is relevant in diseases like kidney and prostate cancer, where surveillance and other non-surgical interventions exist as alternatives to a potentially complicated surgery. In these scenarios, our modified frailty index augmented by the American Society of Anesthesiologists Risk Class may help inform which patients do not benefit from surgery although this index needs prospective validation.